Bank Mergers & Acquisitions - Amihud, Yakov; Miller, Geoffrey (The New York University Salomon Center Series on Financial Markets and Institutions, 1998)
As the financial services industry becomes increasingly international, the more narrowly defined and historically protected national financial markets become less significant. Consequently, financial institutions must achieve a critical size in order to compete. Bank Mergers & Acquisitions analyses the major issues associated with the large wave of bank mergers and acquisitions in the 1990's. While the effects of these changes have been most pronounced in the commercial banking industry, they also have a profound impact on other financial institutions: insurance firms, investment banks, and institutional investors. Bank Mergers & Acquisitions is divided into three major sections: A general and theoretical background to the topic of bank mergers and acquisitions; the effect of bank mergers on efficiency and shareholders' wealth; and regulatory and legal issues associated with mergers of financial institutions. It brings together contributions from leading scholars and high-level practitioners in economics, finance and law